The Correlation Among Poverty, Crime and Unemployment - Gavelis, Vytautas (Ekonomika, 1999)
After the restoration of Lithuania’s independence the hopes of most people were related to the merits of private property and market economy. However people hoped for rapid prosperity in vain. Meanwhile crime has been increasing. In the period of 1990-1997 in Lithuania crime rates grew twice and the trend continues upwards. Moreover official statistic data hardly reflect while collar crimes although material damage is estimated at billions Litas. The analysis has proved that in the period of transition from command economy to market economy it is impossible to avoid the growth of crime rates. The phenomenon is peculiar to the period. The occurrence of private property, unemployment, inflation, competition divided the society according to the level of prosperity as well as according to the possibilities to reach one or another step of the social ladder. The reason for property crimes and other negative crime trends were determined by the insufficiency of possibilities of society members to preserve and improve prosperity. The main cause of economic crimes in the period of transition is the low level of economic mobility of the major part of residents. Economic mobility is a persons ability to improve or aggravate his/her social economic conditions of living, to increase or decrease his/her personal and subsequently household income. Crime is determined by the absence of possibilities to get out of poverty. Statistic data indicate that there is a strong correlation between crime and unemployment. Crime follows unemployment. The policy of unemployment reduction should be based on untraditional measures. The stale should gradually decrease the direct and indirect subsidies which are hardly effective and begin to build modem industrial enterprises using the stale’s funds and later transmit them freely or rent to any Lithuanian or foreign businessperson who would bind himself/herself to sell all the production abroad.